Determinan Struktur Modal: Peran Volatilitas Laba, Struktur Aset dan Fleksibilitas Keuangan - Agustin, Nia Agustin; Zaretta, Bara (JURNAL ILMIAH MANAJEMEN & BISNIS, 2025)
Purpose – This study aims to examine the impact of earnings volatility, asset structure, and financial flexibility on capital structure in automotive sector companies listed on the Indonesia Stock Exchange during the period 2019–2023.Methodology – This research employs a quantitative approach, analysed using SPSS with multiple linear regression analysis. The sample was selected using purposive sampling, resulting in 11 companies as the research sample.Findings – The results indicate that asset structure has a positive and significant effect on capital structure, suggesting that a higher proportion of fixed assets increases a company's tendency to utilise debt. Conversely, earnings volatility and financial flexibility have a negative and significant effect on capital structure. Companies with unstable earnings and high financial flexibility tend to reduce reliance on debt financing. These findings provide important implications for management in designing optimal financing policies.Originality/Novelty – This study develops a model by incorporating financial flexibility, earnings volatility, and asset structure as independent variables to analyse their effect on capital structure. The uniqueness of this research lies in its focus on the automotive sector, which is characterized by high fixed asset intensity and fluctuating income. These characteristics make financial flexibility a crucial factor in financing decisions, which has not been widely examined specifically within the context of the automotive industry in Indonesia.Implications – The research findings indicate that asset structure drives an increase in capital structure, while earnings volatility and financial flexibility decrease it. Therefore, automotive companies are advised to optimise fixed assets, maintain earnings stability, and strengthen financial flexibility to reduce dependence on debt. Adaptive financial strategies, such as collaboration and joint investments, are important to strengthen the financial position amid the dynamics of the industry.